Impact of non-smoking ordinances on hospitality revenues: The case of Germany - Gabriel M. Ahlfeldt; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2009)
Non-smoking ordinances are among the most popular albeit controversial public health-care legislations worldwide. This article provides an empirical assessment of the impact of non-smoking ordinances on bar and restaurant revenues in German Federal States. By application of panel spline regression and difference-in-difference strategies, we find negative impact limited to bars in the very short run. If any, there is a positive impact on total expenditures in the long run, indicating that either consumption pattern has not changed at all or that any reduction in spending by smokers is compensated for by a corresponding increase by non-smokers. These findings support the German and similar non-smoking legislations in the sense that positive externalities resulting from reduced health care cost are likely to outweigh the risk to businesses in the hospitality sector, at least in the long run.
Keywords: I18; K32; 330; Bar Revenues; Non-smoking Ordinances; Restaurant Revenues